Impact of Training & Development in Public Sector Enterprises (A Case Study of BHEL & HMT) - Singh, Smita; Yadav, D. R. (Journal of Commerce and Trade, 2014)
Training and development refers to the practice of providing training, workshops, coaching, mentoring, or other learning opportunities to employees to inspire, challenge, and motivate them to perform the functions of their position to the best of their ability and within standards set by local, state, Tribal, Federal and licensing organization guidelines. Training and development activities provide all involved system of care parties with the tools they need to develop professionally, increase their knowledge, effectively work with families, and build their capacity to perform the tasks associated with their positions within the system of care. Since a system of care operates within an existing human service agency, it is expected that most human resource issues, such as hiring, benefits, staff recognition, and performance appraisal issues, would be handled within the agency’s human resources department. It would be important to make sure that system of care principles are infused into the day to day practices of human resources personnel. It is worth noting that many systems of care have developed recognition and award programs for individuals who have exceeded expectations in their system of care efforts.